Ответ: a ) 20 ; b ) 17 .
Пошаговое объяснение:
a ) ( 6√300 - 2/3 √27 + 2/5 √75 ) : 3√3 = (6 *10√3 - 2/3 *( 3√3 ) +
+ 2/5 *( 5√3 ) ) : 3√3 = ( 60√3 - 2√3 +2√3 ) : 3√3 = ( 60√3) : ( 3√3) =20 ;
b ) ∛45 * ∛- 75 + 48^( 1/4) / 3^( 1/4) = ∛(- 45*75 ) + ( 48 / 3 )^(1/4) = ∛( 27 * 125) +
+ 16^(1/4) = 3 * 5 + 2 = 17 .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: a ) 20 ; b ) 17 .
Пошаговое объяснение:
a ) ( 6√300 - 2/3 √27 + 2/5 √75 ) : 3√3 = (6 *10√3 - 2/3 *( 3√3 ) +
+ 2/5 *( 5√3 ) ) : 3√3 = ( 60√3 - 2√3 +2√3 ) : 3√3 = ( 60√3) : ( 3√3) =20 ;
b ) ∛45 * ∛- 75 + 48^( 1/4) / 3^( 1/4) = ∛(- 45*75 ) + ( 48 / 3 )^(1/4) = ∛( 27 * 125) +
+ 16^(1/4) = 3 * 5 + 2 = 17 .